THE FORMATION OF PHONETIC COMPETENCE OF ARTIFICIAL BILINGUAL BY MEANS OF INNOVATIVE TECHNOLOGIES - Valeria Andreevna Boldyreva; Tatiana Nikolaevna Lomteva (Вестник Северо-Кавказского федерального университета, 2022)
This article is devoted to problems of software training and application of innovative technologies in the framework of learning a foreign language. Problems of chosen topic are very relevant in connection with the failure of research in thefield of phonetics andphonology associated with the formation of the phonetic competence of artificial bilingual not only through the use of standard pedagogical linguistic tactics and techniques such as practicing the sounds and intonation patterns with the help of tongue twisters in the foreign language, but with a new and specialized linguistic software. In this article, we are going to conduct an experiment on introduction of the audio software Praat 6.0.20 in the process of conducting practical training on formation ofprimary phonetic skills. The results allow us to hypothesize about the usefulness of this application for the formation ofphonetic competence in the conditions of artiicial bilingualism.